O PRIMEIRO CONTACTO COM A PROFISSÃO DOCENTE: EXPERIÊNCIAS DE UM FUTURO PROFESSOR DE EDUCAÇÃO FÍSICA - Luís Miguel Gomes da Silva Peixoto (2022)
The present report is about the experiences lived by a preservice teacher (the author), in the last step of his academic education, the Professional Internship. This moment, that ends the cycle of studies in Teaching Physical Education in Basic and Secondary School System of the Faculty of Sports of the University of Porto, marks the transition to the professional life as a Physical Education Teacher. In this specific case, all the pedagogical action was taken between two schools in Barcelos, under the supervision of the cooperating and guiding teachers. In this report, there are registered many challenges, difficulties and learnings, that made this path unique and special, contributing to the personal and professional development of the author. The experiences narrated reveal all the work made by the author, showing the impact that his pedagogical action had in his students and how they were steered in acquiring significant learnings, always in attention to their needs and difficulties. In the professional development, a study was conducted with the main objective of understanding which game forms in the football modality are more beneficial for a more active and intense class. The study showed that every game form used was a good task for learning and improved a dynamic and intense class; that the game forms that used a forward goal keeper were more beneficial for higher intensity; and that there were not significantly statistical differences in the game forms used. Lastly, this school year was very memorable, all these experiences made possible various and great lessons that were fundamental for the development of the professional and personal identity of the author. KEY